IMPROVING PROJECT TIME ESTIMATION IN GAME DEVELOPMENT: RAYLEIGH DISTRIBUTION AND PROGRAM EVALUATION AND REVIEW TECHNIQUE APPROACH - Haikal Ghiffari, Mochamad
The video game industry has grown exponentially over the past few decades, becoming a dominant force in the global entertainment sector. Despite its rapid growth, the game development process remains highly complex and distinct from traditional software development, requiring a creative and agile approach. One key challenge is the inaccurate time estimation in game development projects, which often results from the inherent uncertainty in the iterative and creative nature of the industry. This paper addresses this issue by integrating the Critical Path Method (CPM) and the Program Evaluation and Review Technique (PERT) with the Rayleigh distribution to improve accuracy under high uncertainty conditions. Data from a completed game development project by an Indonesian game company, PT. ABC, is analyzed, with historical data from Project Black (October 2023 – August 2024) serving as the basis for evaluation. The results show that the Rayleigh-PERT model, with 70% confidence and an expert quality estimate of 0.3, provides the most accurate time estimation, achieving only a 4.26% deviation from actual project performance, significantly outperforming CPM (20%) and traditional PERT (15.2%). This research contributes to improving project management in the video game industry by incorporating uncertainty into time estimation, offering more realistic schedules for game development projects, and enhancing overall project execution. However, the study's scope is limited to Project Black by PT. ABC, and further research is required to validate generalizability to other projects or industries.